Development of Audio Visual Basic Big Book Media to Overcome Dyslexia Students in SDN 034788 Panji Dabutar - Icha Peratiwi Sihotang; Sapri Sapri; Andina Halimsyah Rambe (Education Achievement: Journal of Science and Research, 2024)
This research aims to find out whether the Big Book for dealing with dyslexic students is feasible, practical and effective in the learning process. This research uses the Research and Development (RnD) research method with a 4D model (Define, Design, Develop, Dessiminate). The instruments used in this research were interview sheets, validation sheets for media experts, material experts, language experts, questionnaires for homeroom teacher responses and student responses as well as tests conducted pretest-posttest to see the effectiveness of the Big Book in overcoming dyslexic students.  The results of this research show that what has been developed received a percentage of 84.16% (media experts), 93.3% (material experts), as well as 100% (homeroom teacher response) and 93% (student response) with very practical criteria. Big Book was also declared effective as seen from the achievement of N-Gain results by getting an N-gain score of 16.44 with an average N-Gain score of 0.782857 with an N-Gain score percentage of 78.28%. Based on the presentation of the results above, it is stated that the Big Book for overcoming dyslexia that has been developed is feasible, practical and effective for use in the learning process. The Big Book developed can help students who have difficulty reading and teachers can use the Big Book as teaching material in the classroom.